2018
DOI: 10.1002/ijgo.12631
|View full text |Cite
|
Sign up to set email alerts
|

Doppler and biochemical assessment for the prediction of early pregnancy outcome in patients experiencing threatened spontaneous abortion

Abstract: Serum progesterone and CA125 are useful provisional predictors of spontaneous abortion, whereas the Doppler indices are not. The two biomarkers could be used as a basis to counsel anxious couples. CLINICALTRIALS.GOV: NCT02420769.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Sheehata et al [21] found no significant difference between the Doppler indices of the uterine artery. The patients' ages were significantly higher in the spontaneous abortion group than in the ongoing pregnancy group, which is consistent with previous studies reporting that inappropriate and inadequate progesterone secretion increases miscarriage rate due to ovarian aging [21,22]. In our study, age was significantly higher in the threatened miscarriage group and no significant differences were found in the indexes of spiral and uterine arteries by Doppler ultrasonography.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sheehata et al [21] found no significant difference between the Doppler indices of the uterine artery. The patients' ages were significantly higher in the spontaneous abortion group than in the ongoing pregnancy group, which is consistent with previous studies reporting that inappropriate and inadequate progesterone secretion increases miscarriage rate due to ovarian aging [21,22]. In our study, age was significantly higher in the threatened miscarriage group and no significant differences were found in the indexes of spiral and uterine arteries by Doppler ultrasonography.…”
Section: Discussionmentioning
confidence: 92%
“…When spiral artery RI is normal, decreased uterine artery RI in the placental area may occur with a locally developing shunt [20]. Sheehata et al [21] found no significant difference between the Doppler indices of the uterine artery. The patients' ages were significantly higher in the spontaneous abortion group than in the ongoing pregnancy group, which is consistent with previous studies reporting that inappropriate and inadequate progesterone secretion increases miscarriage rate due to ovarian aging [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of uterine artery blood flow can be performed in the second or third trimester to assess if the pregnancy is progressing normally; however, its value in the early first trimester is controversial. Some investigators have reported that an increased uterine artery pulsatility index (UTPI) or resistant index (RI) at between 6 and 12 weeks of pregnancy may precede the diagnosis of a miscarriage, 8,9 whereas other investigators have been unable to confirm this finding 10–12 . Earlier studies did not precisely time the assessment of uterine artery blood flow, ranging from 6–14 weeks of pregnancy, 8–10,12 which could have introduced bias and increased the variance of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that an increased uterine artery pulsatility index (UTPI) or resistant index (RI) at between 6 and 12 weeks of pregnancy may precede the diagnosis of a miscarriage, 8,9 whereas other investigators have been unable to confirm this finding. [10][11][12] Earlier studies did not precisely time the assessment of uterine artery blood flow, ranging from 6-14 weeks of pregnancy, [8][9][10]12 which could have introduced bias and increased the variance of the results.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization [WHO], "abortion is defined as loss of a pregnancy before 20 weeks of gestation" [1] . Doppler ultrasound supply is used to measure blood velocity and flow [2] .…”
Section: Introductionmentioning
confidence: 99%